2017
DOI: 10.1177/1077800417742411
|View full text |Cite
|
Sign up to set email alerts
|

Making Claims that Matter: Heuristics for Theoretical and Social Impact in Qualitative Research

Abstract: Scholar activists draw on a variety of theoretical, methodological, and practical tools for creating and sustaining social justice. We argue that data analysis—in addition to research design, participation, and community engagement—can be leveraged to engage in scholarship for social good. This essay contributes to that effort by offering a set of data analytic heuristic devices for qualitative researchers. These heuristic devices include community cocktail party, conjecturing claims, Jeopardy research questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Along with the current study findings, Huffman and Tracy (30) found that significant improvement was detected in nurse managers' resonant leadership practice after program implementation there with their nurses. Also, Brouer and Harris (31) stated that resonant leaders are aware of the power of using emotional intelligence to persuade staff members to be more dedicated to their work and the organization's objectives.…”
Section: Discussionsupporting
confidence: 78%
“…Along with the current study findings, Huffman and Tracy (30) found that significant improvement was detected in nurse managers' resonant leadership practice after program implementation there with their nurses. Also, Brouer and Harris (31) stated that resonant leaders are aware of the power of using emotional intelligence to persuade staff members to be more dedicated to their work and the organization's objectives.…”
Section: Discussionsupporting
confidence: 78%
“…During this process, two negative cases emerged (i.e., participant perspectives that diverged and opposed other participant perspectives). We conducted a negative case analysis for each of the negative cases to understand why their perspectives were unique to the other participants (Huffman & Tracy, 2018). Those analyses are included in the findings section.…”
Section: Discussionmentioning
confidence: 99%
“…Partners should engage in a dialogue where each has equal opportunities to share their expertise on a topic of interest, identify information gaps, and generate specific questions. Drawing from multiple perspectives can enrich researchers' understanding of a problem by offering varying perspectives and building understanding of the context in which the problem occurs (Huffman & Tracy, 2018). In this process, the academic researcher plays a central role in bringing together the various partners' perspectives, injecting an evidence-base into the conversations, and translating ideas into formal research questions.…”
Section: Facilitating Engagement Of All Partners With Research Questionsmentioning
confidence: 99%